强直性肌营养不良Ⅰ型患者的临床评分与病理改变的相关性 - 汪伟; 刘祺; 王朝霞; 张巍; 袁云 (中华医学杂志, 2013)
目的 报道强直性肌营养不良1型(DMl)患者的骨骼肌受累分级评分(MIRS)与病理改变的关系.方法 选择自2003年5月至2011年6月就诊于北大医院神经内科诊断为DM1的46例先证患者为研究对象,其中男30例,女16例,起病年龄在10～57岁,起病至确诊病程4个月至35年.主要表现为肢体远端力弱,伴随肌强直、斧头脸以及其他系统损害.对临床表现进行MIRS评分,对其肱二头肌进行骨骼肌病理检查,分析MIRS评分和与肌纤维直径变异、核内移程度、破碎红纤维出现率、间质增生、肌浆块出现率之间的关系,统计MIRS分级≥4及≤3两组患者间上述病理改变的差异.结果 46例患者MIRS评分1级0例、2级8例、3级14例、4级23例、5级1例.MIRS评分和肌纤维直径变异(r=0.305,P=0.039)、核内移程度(r=0.451,P=0.002)、破碎红纤维出现率(r=0.364,P=0.013)存在显著相关性,与间质增生、肌浆块均无显著相关性.MIRS分级≥4及≤3的两组患者间核内移程度差异有统计学意义(P=0.006)、破碎红纤维出现率差异有统计学意义(P=0.0048),间质增生、肌浆块以及肌纤维直径变异在两组间差异无统计学意义.结论 MIRS评级具有一定的骨骼肌病理改变基础,特别是核内移和破碎红纤维改变. To explore the relationship between muscular impairment rating scale (MIRS) and myopathological changes of myotonic dystrophy type 1 (DM1).A total of 46 patients at our hospital from May 2003 to June 2011 were diagnosed as DM1. There were 30 males and 16 females. The age of onset ranged from 10 to 57 years old. The major symptoms included distal extremity weakness and myotonia. They were assessed with MIRS and muscle biopsies. The relationship was examined between MIRS and the variation of fiber size, central nuclear, ragged red fibers, proliferation of connective tissue, sarcoplasmic mass. Statistic analysis of pathological changes was made between the groups of MIRS ≥ 4 and ≤ 3.The scores of MIRS were 2 (n = 8), 3 (n = 14), 4 (n = 23) and 5 (n = 1). MIRS had significant correlations with variations of fiber size (P = 0.039, r = 0.305), degree of nuclear translocation (P = 0.002, r = 0.451) and ragged red fibers (P = 0.013, r = 0.364). But there was no significant correlation with the proliferation of connective tissue and sarcoplasmic mass. There were significant differences in nuclear translocation and ragged red fibers. But no significant difference existed in variations of fiber size between the groups of MIRS ≥ 4 and ≤ 3.The rating scale of MIRS has a certain myopathological basis, especially with regards to the changes in nuclear translocation and ragged red fibers. PubMed 中文核心期刊要目总览(PKU) 中国科技核心期刊(ISTIC) 中国科学引文数据库(CSCD) 0 7 508-511 93